plaNext - Feras Hammami (PlaNext, 2016)
This volume marks an important stage in plaNext. It publishes original works following an open call, as the special-issue inaugural volume was dedicated to selected contributions from the 8th AESOP-YA annual conference. With the growing interest in plaNext, we see a bright future as a leading open access journal in planning and other related fields. Thanks to the generous contribution of AESOP, all articles are openly available at AESOP’s digital platform, InPlanning, and authors do not pay any article processing fee. In this respect, we envision plaNext as an effort by the young academic community of AESOP to help free the dissemination of knowledge from any unjust global academic system.